Dienogest therapy during the early stages of recurrence of endometrioma might be an alternative therapeutic option to avoid repeat surgeries. Issue 10 (10th July 2018) - Koshiba, Akemi; Mori, Taisuke; Okimura, Hiroyuki; Akiyama, Kanoko; Kataoka, Hisashi; Takaoka, Osamu; Ito, Fumitake; Matsushima, Hiroshi; Kusuki, Izumi; Kitawaki, Jo
Abstract: Aim: We aimed to evaluate whether hormonal therapy immediately after postsurgical recurrence of ovarian endometrioma controls disease progression and can be an alternative therapeutic option to avoid multiple repeat surgeries. Methods: We enrolled 146 patients treated for endometrioma at the University Hospital of Kyoto Prefectural University of Medicine between 2009 and 2015. After laparoscopic cystectomy using the stripping technique, opening of cul‐de‐sac obliterations and complete resection of the deep infiltrating endometriosis lesions, the patients either received no treatment ( n = 83), oral contraceptives (OC; n = 32) or dienogest (DNG; n = 27), depending on their medical history. Four patients were excluded because they changed their regimens during the follow‐up period. All patients were followed up every 3 months. Patients who developed recurrence of endometrioma immediately received DNG, OC or gonadotropin‐releasing hormone agonist. Results: Overall, 16 patients developed a recurrence of the endometrioma (12 in the nontreatment group, three in the OC group and one in the DNG group). The 11 patients with recurrence were treated with DNG immediately after the diagnosis of recurrent endometrioma. Among them, seven patients continued treatment with DNG (2 mg) for 24 months. After 24 months of treatment with DNG, complete resolution of recurrent endometrioma was achieved in four (57.1%) of seven patients. There was no improvement in the three patients who received OC and one patient who underwent secondary surgery. Conclusion: DNG therapy early after recurrence of postsurgical endometrioma appears to be viable for reducing the risk of repeated surgery.